2011
DOI: 10.1521/aeap.2011.23.3_supp.17
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of First-Time and Repeat HIV Tests Among Men Who Have Sex With Men Who Test at CDC-Supported Sites, 2007

Abstract: This report describes characteristics of HIV test data for men who have sex with men (MSM) tested in 2007 through programs funded by the Centers for Disease Control and Prevention (CDC). HIV test-level data of MSM submitted by 29 health departments were analyzed to explore test characteristics among all tests, first-time tests, and repeat tests. Characteristics significantly associated with HIV-positive results among first-time tests were identified through logistic regression. Of the 129,893 tests conducted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…22 However, they were lower than the proportions reporting a history of HIV testing found among urban MSM in high-income countries like Japan (Yokohama), United Kingdom (London), and United States (several cities) where proportions were more than 60%. [23][24][25] We anticipate the proportion of MSM with repeat HCT will continue to increase as HCT is further promoted, hopefully resulting in an increase in the proportion of MSM who repeat HCT within 180 days.…”
Section: Discussionmentioning
confidence: 99%
“…22 However, they were lower than the proportions reporting a history of HIV testing found among urban MSM in high-income countries like Japan (Yokohama), United Kingdom (London), and United States (several cities) where proportions were more than 60%. [23][24][25] We anticipate the proportion of MSM with repeat HCT will continue to increase as HCT is further promoted, hopefully resulting in an increase in the proportion of MSM who repeat HCT within 180 days.…”
Section: Discussionmentioning
confidence: 99%
“…This represents the biggest study to date analyzing the associations between repeat testing and risk behavior in repeat testers. In 2007, repeat testers accounted for more than 80 % of HIV tests performed annually in the United States [ 1 ], and when analyzing our program since 2008, repeat tests accounted for 48 % (8,396/17,333) of voluntary HIV tests among MSM. Our main finding was that repeat acute infection screening (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Men who have sex with men (MSM) bear the greatest burden of HIV infection in California and the United States [ 1 5 ]. The Center for Disease Control and Prevention recommends that high-risk groups, like sexually active MSM, receive HIV testing and counseling at least annually [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“… 6 MSM bear the greatest burden of HIV infection in California and the United States. 7 9 But while MSM represent a significant risk group, the risk of HIV infection within this population is not uniform. Studies have shown that MSM presenting to community HIV-screening programs may represent a subsegment of the MSM population at higher risk for the acquisition of HIV infection.…”
Section: Introductionmentioning
confidence: 99%